STRATEGIES FOR IMPROVING STUDENT QUALITY IN PHRAPARIYATTHAM WAT KOK PIEW SCHOOL SONGKHLA PROVINCE - Sukijjo (Chotikarn), Phrakrusamuh Krittapas; Sumeto, Phramahasupot; Onkong, Samit (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were: 1) study the teaching environment of Buddhist schools. 2) Develop a student quality development strategy for Phrarariyattidhama School 3) Propose a student quality development strategy for Phrarariyattidhama School. This study is a qualitative research, collecting data through in-depth interviews with 15 participants/people and 9 key informants/people. A group discussion was conducted by 14 experts/individuals, and through inductive data analysis, the research results showed that: 1) The strongest internal environment is lies in the management personnel meeting. The weakest internal environment was a employees have a lot of courses and other workloads. The external environment was opportunity houses, temples, schools, and local government organizations cooperate for preserve culture. The external environment was threat people still lack knowledge and understanding Buddhist scripture education method 2) The result of formulating a strategy for the development of students’ quality in Phrarariyattidhama schools. Conduct internal and external environmental assessments based on the ’pest’ model to improve students’ quality. 3) The outcome of the strategic statement. Experts believe that this is possible, appropriate, and useful. These four strategies include: 1) improving learners’ quality to meet standards; 2) utilizing the concept of full economy to develop learning process courses. 3) Train teachers and personnel to organize high-quality learning activities. 4) Improve school management efficiency based on good governance. Pay attention to the participation of all departments.